2014
DOI: 10.1179/1743284714y.0000000602
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of impact toughness of simulated heat affected zone by addition of aluminium

Abstract: The effect of aluminium content (0?023, 0?038 and 0?070 wt-%) on microstructure and impact toughness of simulated coarse grained heat affected zone (CGHAZ) of high strength low alloy steels with different heat inputs (20, 100 and 200 kJ cm 21 ) was investigated. The microstructure of simulated CGHAZ consisted of predominantly granular bainite. The martensite-austenite constituents became finer and its volume fraction decreased with increasing aluminium content, irrespective of heat input level. The impact toug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Less carbon atoms in transformed ferrite drove ferrite growing up more easily and the carbon-rich area was compressed accordingly. 24,25 Therefore, the increase in second heat input resulted in the increase of slender M-A constituent and reduction of blocky M-A. The relationship between the Charpy impact energy at −20°C and volume fraction of M-A constituent is shown in Fig.…”
Section: Effect Of M-a Constituent At Different Heat Input On Toughnessmentioning
confidence: 97%
“…Less carbon atoms in transformed ferrite drove ferrite growing up more easily and the carbon-rich area was compressed accordingly. 24,25 Therefore, the increase in second heat input resulted in the increase of slender M-A constituent and reduction of blocky M-A. The relationship between the Charpy impact energy at −20°C and volume fraction of M-A constituent is shown in Fig.…”
Section: Effect Of M-a Constituent At Different Heat Input On Toughnessmentioning
confidence: 97%
“…It was reported that even the slight variation in fraction and size of M-A constituents can affect the impact toughness of CGHAZ significantly. 23 Because the addition of aluminium increases the fraction of retained austenite in M-A constituents, and then decreases the fraction and size of M-A constituents consequently, it can be proposed that the addition of small amount of aluminium will improve the impact toughness of CGHAZ effectively.…”
Section: Morphology and Size Distribution Of M-a Constituentsmentioning
confidence: 99%
“…Effect of Al addition on the base metal and HAZ toughness has been reported several researchers in the viewpoint of a carbide precipitation 1,2) , a M-A constituent formation 1,3) , and a rejection of free nitrogen [4][5][6] as a function of Al content and welding heat input. Fukuda 1) investigated the effect of 0.015wt%Al-addition to 0.1C-0.2Si-1.4Mn-0.01Ti steel which showed lower crack tip opening displacement (CTOD) compare to ultra-low Al (<0.001w%) steel in the submerged arc welded multi-pass heat affected zone due to the promotion of bainite and M-A constituent, rather than ferrite and cementite.…”
Section: Introductionmentioning
confidence: 99%
“…Mintz 6) reported that effect of Al content on the strength and toughness of (0.02, 0.1%C)-(10,40ppm N) steel, and concluded that HAZ toughness was increased with 0.2%Al as a result of cementite refinement and rejection of free nitrogen with no significant change of the strength. As described above, all of the test reports about weld HAZ have limited to the steels containing Al less than 0.07wt% 1,[3][4][5] while the steels that contain Al higher than 0.1wt% show quite good toughness 2,6) due to the various beneficial effect of Al addition.…”
Section: Introductionmentioning
confidence: 99%